Selectivity switch between FAK and Pyk2: Macrocyclization of FAK inhibitors improves Pyk2 potency. Issue 24 (15th December 2016) - Farand, Julie; Mai, Nicholas; Chandrasekhar, Jayaraman; Newby, Zachary E.; Van Veldhuizen, Josh; Loyer-Drew, Jennifer; Venkataramani, Chandrasekar; Guerrero, Juan; Kwok, Amy; Li, Ning; Zherebina, Yelena; Wilbert, Sibylle; et al.
Graphical abstract: Abstract: Herein, we describe the synthesis of Pyk2 inhibitors via macrocyclization of FAK and dual Pyk2-FAK inhibitors. We identified macrocycle25a as a highly potent Pyk2 inhibitor (IC50 = 0.7 nM), with ∼175-fold improvement in Pyk2 potency as compared to its acyclic counterpart. In many cases, macrocyclization improved Pyk2 potency while weakening FAK potency, thereby improving the Pyk2/FAK selectivity ratio for this structural class of inhibitors. Various macrocyclic linkers were studied in an attempt to optimize Pyk2 selectivity. We observed macrocyclic atropisomerism during the synthesis of 19-membered macrocycles10a –d, and successfully obtained crystallographic evidence of one atropisomer (10a-AtropB ) preferentially bound to Pyk2.